Towards Detecting Climate Change Effects With UAV-Borne Imaging Radars - Ingrid Ullmann; Christina Bonfert; Alexander Grathwohl; Mohamed Amine Lahmeri; Victor Mustieles-Perez; Julian Kanz; Elena Sterk; Frederik Bormuth; Roghayeh Ghasemi; Patrick Fenske; Michelangelo Villano; Robert Schober; et al. (IEEE Journal of Microwaves)
Climate change is associated with a variety of environmental phenomena, such as the melting of glaciers, the drying out of crops and soils, and an increase in the risk of avalanches. To detect and monitor these changes, satellite-based radar imaging is widely used, as it enables the large-scale mapping of the Earth's surface independent of weather and sunlight. An emerging field of research is to use radar systems mounted on unmanned aerial vehicles (UAVs) for this purpose. UAV-borne radar systems image smaller areas, but can capture them in greater detail, more flexibly in terms of flight trajectory, and at shorter repetition intervals. This article presents the capabilities of UAV-based radar systems and the associated challenges in terms of system design and imaging techniques for detecting and monitoring the effects of climate change. Current research results are shown. In addition, we give an outlook on using a swarm of cooperative UAVs, each carrying a radar. UAV swarms will enable a higher imaging quality with respect to resolution and detectability, but at the same time come with a number of additional challenges, which will be discussed in the paper as well.